2019
DOI: 10.1111/1440-1681.13164
|View full text |Cite
|
Sign up to set email alerts
|

Galanin receptors activation modulates myocardial metabolic and antioxidant responses to ischaemia/reperfusion stress

Abstract: The neuropeptide galanin comprising 29 amino acid residues (30 in humans) is widely expressed in the central nervous system and peripheral organs and tissues. Galanin exerts its biological activities through three different G protein-coupled receptors, GalR1, GalR2 and GalR3, all of which are found in the heart. 1 Over the past decade, a wealth of data has been accumulated that substantiates targeting galanin receptors for the treatment of various human diseases and pathological conditions, including Alzheimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Alarin was discovered as an alternate transcript of the GALP gene (Santic et al 2006 , 2007 ), and can be detected in circulating blood (Hu et al 2019 ). It showed that galaninergic system can be considered a promising target to reduce energy dysregulation and attenuate oxidative damage in myocardial injury induced by ischaemia/reperfusion (I/R) of rats (Studneva et al 2019b ). An agonist of galanin receptors GalR1-3 can attenuate doxorubicin-induced cardiotoxicity (Studneva et al 2019a ).…”
Section: Introductionmentioning
confidence: 99%
“…Alarin was discovered as an alternate transcript of the GALP gene (Santic et al 2006 , 2007 ), and can be detected in circulating blood (Hu et al 2019 ). It showed that galaninergic system can be considered a promising target to reduce energy dysregulation and attenuate oxidative damage in myocardial injury induced by ischaemia/reperfusion (I/R) of rats (Studneva et al 2019b ). An agonist of galanin receptors GalR1-3 can attenuate doxorubicin-induced cardiotoxicity (Studneva et al 2019a ).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac assays have also been performed on mammals. Studneva et al (2019) administered forms of galanin to myocardial injury-induced rats and recorded blood pressure and heart rate in vivo.…”
Section: Physiology-based Functional Studiesmentioning
confidence: 99%
“…To eliminate oxidative stress, antioxidants are promising candidates for I/R injury therapy. Thus, it is noteworthy to evaluate the association between the pharmacodynamics effects of antioxidants and I/R injury alleviation (Studneva et al, 2019). Antioxidants inhibit reactive oxygen species (ROS) emission and apoptosis induction (Xiao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%